Le « Sertão » du « Nordeste » (Brésil). Essai de définition d’un « pays ». - Hamelin, Louis-Edmond (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1958)
Despite the fact that Brazil is a young and vast country, some of its regions have already acquired a personality of their own. The Sertâo in the Northeast is such a case. Of triangular shape, the Sertâo opens in the North, towards the Atlantic ocean ; it covers 10% of the total area of Brazil and include more than 90% of the states of Rio Grande do Norte, Ceara and Paraiba. It is a semi arid region with a dry climate, chiefly responsible for an original type of vegetation : the caatinga. The fundamental features of the relief are horizontal with depressions and inselbergs. The rare good soils are deteriorated and the hydrographic network is fair. Such a severe country is inhabitated by 7 millions persons of mixed ethnic origins. The dominant occupational types, are the vaqueiro, the garimpeiro, the truck driver , and, during the dry season, the flagellado. It is an « under-developped » country economically , with low standards of living, and a production based on food and cattle. If the Sertao is unsafe foreigners, it remains for the natives, a mystical and attractive country that may become more prosperous with the hydro-electric development of the Sao Francisco River.